2001
DOI: 10.1002/jms.231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eluent on the ionization efficiency of flavonoids by ion spray, atmospheric pressure chemical ionization, and atmospheric pressure photoionization mass spectrometry

Abstract: The effect of nine different eluent compositions on the ionization efficiency of five flavonoids was studied using ion spray (IS), atmospheric pressure chemical ionization (APCI), and the novel atmospheric pressure photoionization (APPI), in positive and negative ion modes. The eluent composition had a great effect on the ionization efficiency, and the optimal ionization conditions were achieved in positive ion IS and APCI using 0.4% formic acid (pH 2.3) as a buffer, and in negative ion IS and APCI using ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
113
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(118 citation statements)
references
References 40 publications
2
113
1
2
Order By: Relevance
“…Greater sensitivity has been reported in the negative ion mode than in the positive ion mode [21,30,31,38], a factor attributed to the substantial acidities of flavonoids and the ease of deprotonation due to their multiple hydroxyl groups. However, the CAD spectra of deprotonated flavonoid glycosides generally show few fragments, and are therefore not particularly useful for isomer differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater sensitivity has been reported in the negative ion mode than in the positive ion mode [21,30,31,38], a factor attributed to the substantial acidities of flavonoids and the ease of deprotonation due to their multiple hydroxyl groups. However, the CAD spectra of deprotonated flavonoid glycosides generally show few fragments, and are therefore not particularly useful for isomer differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have reported characterization of flavonoids by electron ionization (EI) [6 -10] or fast atom bombardment (FAB) mass spectrometry [7,[11][12][13][14][15][16][17][18][19]. More recently, electrospray ionization (ESI) [19 -29], atmospheric pressure chemical ionization (APCI) [27][28][29][30][31], and matrix-assisted laser desorption ionization (MALDI) [32,33] have been used to analyze flavonoids, typically in conjunction with tandem mass spectrometry (MS/MS) or high-performance liquid chromatography (HPLC). Despite these inroads, mass spectrometric analysis has not yet reached the point where de novo identification of flavonoids is possible.…”
mentioning
confidence: 99%
“…Acetic acid was added in the mobile phase to improve the ionization of homoisoflavonoids, though they did not alter their chromatographic retention significantly° [22].…”
Section: Hplc-dad-esi-ms N Analysis Of the Plant Extractmentioning
confidence: 99%
“…Tanaka et al [21] reported LODs in the range of 25-50 mg/mL for basic drugs analyzed by CE-APCI/MS. APPI was introduced by Robb et al in 2000 [25] as a complement to ESI and APCI to broaden the range of ionizable analytes in API techniques [26,27] and has been adapted for the analysis of nonpolar compounds [25,[28][29][30][31][32]. Technically, the APPI source is similar to APCI, i.e., the sample is vaporized in a heated nebulizer before ionization and nonvolatile salts can be easily removed during this step.…”
Section: Introductionmentioning
confidence: 99%